EFFECTS OF CROSSWALK LOCATION AND PEDESTRIAN VOLUME ON ENTRY CAPACITY OF ROUND ABOUTS - JAOETA AKHUL, ASEFA ALMAEHU (International Journal of Multidisciplinary Research and Studies, 2020)
At round about approaches, vehicles must yield to pedestrians who are using crosswalks. The presence of pedestrians using the crosswalk at a roundabout approach thus decreases the entry capacity of the approach. This research used a calibrated microscopic traffic simulation model to check the effect of crosswalk location and pedestrian volume on the capacity of a two-lane approach entering a two-lane roundabout. The simulation results show that (i) at the identical pedestrian volume, the crosswalk located further upstream from the yield line causes a smaller magnitude of reduction within the entry capacity, but there’s no significant change within the entry capacity when the crosswalk is beyond three car-length upstream from the yield line; (ii) for the identical crosswalk location and conflicting volume, the entry capacity reduces with increasing pedestrian volume, but the marginal reduction diminishes with increasing pedestrian volume. Rectilinear regression equations for entry capacity adjustment factor for pedestrians as a function of conflicting volume are developed. The adjustment factors are found to be below the values provided by the Highway Capacity Manual 2010 which is predicated on research conducted in Germany.